Sustaining growth : soil fertility management in tropical smallholdings (Margraf WelkersheimDE, 1994)
Presents a range of practices conducive to sustainable agriculture, including agroforestry; intensive fallowing and green manuring; the use of mulch; compost; stable manure and the deliberate use of natural symbionts.
DC